Numerical Investigation on Turbulent Forced Convection in Heating Channel Inserted with Discrete V-Shaped Baffles - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2016)
The numerical examinations on flow visualization, heat transfer characteristic and performance improvement in a square duct inserted with discrete V-shaped baffles (DVB) are reported. The DVB is designed to reduce the pressure loss when compared with the V-shaped baffle. The influences of the flow blockage ratios (b/H, BR = 0.05-0.20), V-tip directions (V-Downstream and V-Upstream) are investigated for Reynolds number, Re = 3000-20,000, with a single pitch ratio and flow attack angle of 1 and 30°, respectively. As the results, the DVB can generate the vortex flow and impinging flow through the test section that assists to develop the thermal efficiency. The augmentations on the heat transfer coefficient and pressure drop are around 2.5-5.75 and 4-22.5 times above the smooth duct, respectively. The best thermal efficiency in forms of thermal enhancement factor, TEF, around 2.32 is detected at Re = 3000, BR = 0.10 and V-Upstream.
Keywords: Baffle; Forced convection; Heat Transfer Mechanisms